Modelling the economy : based on papers presented at the social science research council's conference on economic modelling at the London graduate school of business studies - Renton, G. A.; Social Science Research Council (U.S.) (London : Heinemann Educational [for] the Social Science Research Council, 1975)
The volume is based on the proceedings of the SSRC Conference on Modelling of the UK Economy held at the London Graduate School of Business Studies in July, 1972. The papers are in different headings like, macro-economic models, forecasting topics, accounts of stimlations experiments, econometric methodology etc.
Includes bibliographical references and index.
rpm 16/11/2017
Loans
Keywords: Economics; Econometric; Forecasting methods; Great Britain